2023
DOI: 10.1523/jneurosci.1723-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Transient and Sustained Ganglion Cell Light Responses Are Differentially Modulated by Intrinsically Produced Reactive Oxygen Species Acting upon Specific Voltage-Gated Na+Channel Isoforms

Abstract: Increasing spike rates drive greater neuronal energy demand. In turn, mitochondrial ATP production leads to the generation of reactive oxygen species (ROS) that can modulate ion channel gating. Does ROS production autoregulate a neuron’s excitability? We investigated the links between retinal ganglion cell (RGC) excitability and spike activity-driven ROS production in male and female mice. Changes to the light- and current-evoked spike patterns of functionally identified αRGC subtypes, along with their NaVchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…For example, in suppressed-by-contrast RGCs, a depolarization block, resulting from a low VGSC conductance, short axonal initial segment (AIS), and selective expression of Na v isoforms (see below), defines the cells’ response ( Wienbar and Schwartz, 2022 ). Another example would be direct (neuro)modulation of Na v function by reactive oxygen species (ROS), as it was recently shown for sustained RGCs ( Smith et al, 2023 ). In complement, our study suggests that the functional properties of VGSCs expressed in tOn-small cells are one of the key mechanisms that shape these cells’ responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in suppressed-by-contrast RGCs, a depolarization block, resulting from a low VGSC conductance, short axonal initial segment (AIS), and selective expression of Na v isoforms (see below), defines the cells’ response ( Wienbar and Schwartz, 2022 ). Another example would be direct (neuro)modulation of Na v function by reactive oxygen species (ROS), as it was recently shown for sustained RGCs ( Smith et al, 2023 ). In complement, our study suggests that the functional properties of VGSCs expressed in tOn-small cells are one of the key mechanisms that shape these cells’ responses.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to identify both baseline and scotopic response changes with Piezo1 activation in the retina, using MEA recording. Increases in excitability drive greater energy demand and can lead to a greater accumulation of metabolic by-products, including reactive oxygen species, from mitochondrial ATP production trying to mitigate the energy imbalance of the RGCs, which in turn may lead to RGC dysfunction 70 . Similar emergence of spontaneous hyperactivity in RGCs has also been detected in animal models of retinal degeneration as the disease progress 7174 .…”
Section: Discussionmentioning
confidence: 99%
“…Acidosis can also trigger a chain of intracellular processes, such as increasing the production of reactive oxygen species (ROS) by mitochondria (Riemann et al, 2011 ). It has been shown that ROS produced by RGCs' mitochondria modulate ion channel gating and excitability (Smith et al, 2023 ). It is also important to remember that RGCs can directly sense pH changes with TWIK-related acid-sensitive K+ (TASK) channels (Zhong et al, 2013 ; Wen et al, 2022 ) and to consider this in planning the research and interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%